Revealing study and breeding implications for production traits and tail characteristics in Simmental cattle by GWAS - Wang, Jie; Shen, Na; Zhao, Kaisen; Liao, Jiayu; Jiang, Genglong; Xiao, Jianghai; Jia, Xianbo; Sun, Wenqiang; Lai, Songjia (Frontiers in Genetics, 2025)
Simmental cattle are renowned for their dual purpose as meat and dairy breeds. The study recorded phenotype data from 183 Simmental cattle and performed a Genome-Wide Association Study (GWAS) analysis to elucidate the genetic mechanisms underlying milk production, body size traits, and tail characteristics. Statistical analysis of phenotype data showed that season, parity, and age at first calving (AFC) factors had a significant effect on milk production (P < 0.05). The results of GWAS on cattle linear traits revealed that the candidate genes SH3RF2, DCHS2, ADAMTS1, CAMK4, PPARGC1A, PRL, PRP6, and CORIN have been found to affect body circumference (BC) and cannon circumference (CC). Through GWAS analysis of tail traits, including Circumference over tail root (COTR) and Tail Length (TL) in Simmental cattle, candidate genes associated with tail length, such as KIF26B, ITPR2, SLC8A1, and SLIT3 were identified. Interestingly, candidate genes IL1RAP, AQP9, ITPR2, and PKD2 were also associated with metabolic inflammation in cattle tails. These genetic markers offer valuable insights into the traits of Simmental cattle, facilitating the development of molecular breeding strategies to enhance production value and provide references for breeding programs.